Beyond exchange : revisiting leadership as a relationship - Epitropaki, Olga; Martin, Robin (Contemporary perspectives on relationship-based leadership, 2025)
"Beyond Exchange: Revisiting Leadership as a Relationship emerged in response to scholarly calls to steer away from the 'exchange' rhetoric and 'give-and-take' conceptualizations in the study of leader-follower interactions and instead shift the focus to the fundamental element of 'relationship'. The book delves into the very essence of leader-follower relationship dynamics, revisits fundamental assumptions of popular relationship-based leadership theories such as Leader-Member Exchange, takes stock of progress made in this research strand, and proposes exciting avenues for future research. This book frames leader-follower interactions as a complex and dynamic relational phenomenon that evolves over time and encompasses a multiplicity of relationship types. Relationships are not static, and one size does not fit all. The book cross-pollinates ideas from other research domains, such as relationship science, and highlights the role of the follower and the importance of affective processes, ethics, and fairness on different levels of analysis. It further extends the notion of leader-follower relationship beyond the dyad to more complex network interactions. We hope readers will find ideas that resonate, and the book helps rekindle scholarly passion for relational phenomena in organizational settings"--